2019
DOI: 10.1155/2019/8963971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Size Distribution on the Critical State of Rockfill

Abstract: In order to study the effect of particle size distribution on the critical state of rockfill, a series of large-scale triaxial tests on rockfill with different maximum particle sizes were performed. It was observed that the intercept and gradient of the critical state line in the e−p′ plane decreased as the grading broadened with the increase in particle size while the gradient of the critical state line in the p′−q plane increased as the particle size increased. A power law function is found to appropriately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…is is consistent with the research results on critical state line of rockfill material [40][41][42].…”
Section: Experimental Characteristics and 3d Description Of Thesupporting
confidence: 93%
See 1 more Smart Citation
“…is is consistent with the research results on critical state line of rockfill material [40][41][42].…”
Section: Experimental Characteristics and 3d Description Of Thesupporting
confidence: 93%
“…Besides, Guo et al found that the particle breakage and particle size distribution had an important effect on the critical state line of the rockfill under stress [38][39][40]. e critical state line of rockfill was very similar to sand.…”
Section: Experimental Characteristics and 3d Description Of Thementioning
confidence: 99%
“…To overcome this problem, a common practice is to prepare test samples by excluding the oversized particles [10,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The method is called the scalping scaling down technique.…”
Section: Introductionmentioning
confidence: 99%
“…The relative breakage index decreases with increasing relative density [14]. Extensive research has also been carried out on the impact of granular materials particle gradation [23][24][25]. For example, model parameters varied linearly with the coefficient of uniformity.…”
Section: Introductionmentioning
confidence: 99%